PENCIPTAAN KOMIK DENGAN GAYA PIXEL ART - Muhammad Dhimas Pratama; Warli Haryana (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2023)
This study aims to create comics with a pixel art visual style by describing the elements and techniques used, to make pixel art style comics, especially in the form of digital comic strips, it requires knowledge of the techniques of making comics and the elements contained in pixel art itself. The method used is a descriptive qualitative approach with a creation methodology used in the making of this article, the creation method in question makes a work product the focus of research by going through three stages, namely (1) Exploration, (2) Improvisation and (3) Formation. The results showed that the technique of making comics used was to determine the story, determine the format, create characters, compose pictures and stories and determine the storyline. While the pixel art techniques or elements implemented are straight lines, dithering, jaggy style or not using anti-aliasing, and inline. Produce six panels with vertical positions measuring 260x150 pixels by paying attention to three visual elements (illustration, typography and color). This writing is expected to contribute ideas in enriching the results of studies on pixel artstyle and can popularize pixel art style as another part of art, especially as comic art. Keywords: comic, digital, pixel art